A Terrific New World : Polar Space in the Narrative, Journals and Letters of John Franklin’s First Arctic Expedition (1819-22) - N. Brazzelli (E-rea, 2014)
Franklin’s first exploration of the Northern coast of Canada captured the public imagination thanks to his Narrative of a Journey to the Shores of the Polar Sea in the Years 1819-22, published in 1823, which conveys the drama of an expedition plagued by harsh weather, bad planning, starvation and even murder. Franklin’s journals and letters written during the expedition, by focusing on planning details and material conditions of travel itself throw fresh light on his much debated mission. Franklin’s texts reveal thus varying perspectives on the events according to the audiences being addressed and the author’s perception of these reading publics. La première exploration de Franklin sur la côte Nord du Canada captiva l’imagination du public grâce à la publication en 1823 de son récit, Narrative of a Journey to the Shores of the Polar Sea in the Years 1819-22. Il y évoque le drame d’une expédition vouée à l’échec par des prévisions erronées et par des conditions climatiques rigoureuses, en proie à la faim et même au meurtre. Les journaux de bord et les lettres écrites par Franklin pendant l’expédition tout en fournissant de nombreux détails sur l’organisation et les conditions matérielles du voyage, éclairent d’une lumière nouvelle une mission encore aujourd’hui controversée. On constate également que les textes de Franklin révèlent différents points de vue sur les événements selon le public auquel ils sont adressés, variations qui dépendent essentiellement de la perception que l’auteur a de ses lecteurs.